Kuliner Melayu di Sumatera Selatan - Maryamah; Ramadhona, Suci; Zannah, Zahratul; Anggraini, Zelvi; Ilbari, Turi Indah (Program Studi PGMI Sekolah Tinggi Ilmu Tarbiyah Nahdlatul Ulama Al Hikmah Mojokerto, 2025)
Cuisine is an essential aspect of cultural heritage, carrying historical value and serving as a marker of local identity. Palembang is widely recognized for its distinctive culinary tradition, particularly pempek, which is not only a wellknown dish but also a symbol embedded in the cultural practices of its people. This article examines the role of cuisine in shaping cultural identity, social differentiation, and economic sustainability, with a specific focus on pempek. Employing a qualitative descriptive approach and literature analysis, this study explores how pempek has evolved from an exclusive royal dish to a widely consumed culinary staple, transcending social and economic classes. Additionally, this research highlights the ritualistic aspects of pempek consumption, its symbolic meanings, and its contribution to the construction of Palembang’s cultural identity. The findings indicate that pempek functions as both a culinary artifact and a cultural marker, reinforcing social identity within the broader discourse of tourism and Indonesia’s culinary diversity. Moreover, the economic impact of pempek is evident in its role within home-based industries and micro-enterprises that sustain local livelihoods. The preservation of traditional cuisine, therefore, is not merely an act of cultural conservation but also a strategic effort to promote regional tourism and economic resilience. Abstrak Kuliner merupakan bagian dari warisan budaya yamg memiliki nilai historis dan identitas lokal. Kota Palembang dikenal dengan kuliner khasnya, salah satunya adalah pempek, yang tidak hanya menjadi ikon Kuliner tetapi juga memiliki makna simbolik dalam tradisi Masyarakat Palembang. Artikel ini membahas peran kuliner sebagai Identitas budaya, diferensiasi soasial, serta dampak ekonominya, dengan fokus pada pempek Palembang. Melalui pendekatan kualitatif deskriptif dan analisis literatur, penelitian ini mengungkap bagaimana pempek berkembang dari makanan istana menjadi hidangan rakyat yang dapat dinikmati semua kalangan. Selain itu, penelitian ini menyoroti keunikan dalam penyajian dan komsumsi pempek, serta peranannya dalam membangun identitas kuliner Palembang. Hasil penelitian menunjukan bahwa pempek bukan sekedar makanan, tetapi juga simbol budaya yang memperkuat identitas Masyarakat Palembang dalam konteks pariwisata dan keberagaman Indonesia. Lebih lanjut, pempek berkontribusi terhadap perekonomian lokal melalui industri rumahan dan isaha mikro yang menompang mata pencarian banyak Masyarakat. Oleh karena itu, pelestarian kuliner tradisional seperti pempek menjadi penting untuk mempertahan kan identitas budaya serta meningkatkan sektor pariwisata dan ekonomi daerah.